Biotype Diversity of Nilaparvata Lugens (Stall) In Several Rice-Producing Areas in North Sumatra - Rani Juniarti Sembiring Maha; Darma Bakti; Marheni (Postgraduate, University of Mataram, 2026)
Nilaparvata lugens is a major rice pest that causes significant losses in Asia. This study aims to identify the diversity of brown planthopper (BPH) biotypes from four rice production centers in North Sumatra, namely Asahan Regency, Batubara Regency, Deli Serdang Regency, and Langkat Regency. Morphologically, the average body length of the macroptera imago was 4.36 mm and that of the brachyptera was 3.51 mm, with antennae consisting of a scape, pedicel, and flagellum. Four samples were tested using PCR with universal primers LCO1490/HCO2198, resulting in amplification of ±700 bp. Sequence and phylogenetic analysis using MEGA 11 showed a genetic distance between samples of 0.000, indicating very close kinship. However, the genetic distance to GenBank data (biotypes 1, 2, 3, and Y) ranged from 0.578 to 0.596, indicating differences in kinship and possible gene mutations or biotype changes. The characteristics of farmers were dominated by those aged 41–50 years, high school education, and the majority being male. The most widely used variety was Inpari-32 (somewhat susceptible to WBC). Most farmers used more than three types of synthetic pesticides, especially in Batubara (96.67%) with a frequency of >3 times per planting season. The intensity of attacks ranged from 1–5%. There was a significant relationship between variety and attack rate (p=0.00). Pests and diseases were the main problems (>50%).